The paper palace - Cowley Heller, Miranda (Riverhead Books, 2021)
"A story of summer, secrets, love and lies: in the course of a singular day on Cape Cod, one woman must make a life-changing decision that has been brewing for decades. Set against the summer backwoods and beaches of Cape Cod, The Paper Palace unfolds over 24 hours and across 50 years, as decades of family legacy, love, lies, secrets, and one unspeakable childhood tragedy lead wife and mother Elle Bishop to the precipice of a life-changing decision. With its transporting setting and propulsive pace, the story draws on the sweet promise of young love, as well as the heartbreaking damage incurred by too many secrets. It's a compulsively readable story about the tensions between the romantic childhood ideals we grow up with, and the family responsibilities that carry us into adulthood. Must our life choices remain irrevocable if the conditions are changed? It is a perfect July morning, and Elle, a fifty-year-old happily married mother of three, awakens at "The Paper Palace"-- the family summer place which she has visited every summer of her life. But this morning is different, because last night Elle and her oldest friend Jonas crept out the back door into the darkness and had sex with each other for the first time, all while their spouses chatted away inside. Now, over the next 24 hours, Elle will have to decide between the life she has made with her genuinely beloved husband, Peter, and the life she always imagined she would have had with her childhood love, Jonas, if a tragic event hadn't forever changed the course of their lives. As Heller colors in the experiences that have led Elle to this day, we arrive at her ultimate decision with all its complexity. Tender yet devastating, The Paper Palace considers the tensions between desire and dignity; the legacies of abuse; and the crimes and misdemeanors of families"--